The Legal Connection between the Discretionary Power of the Administration and the Principle of Proportionality in the Administrative Decision - Hama Karim , Zana Rauf; Abdulkarim , Aso HamaShin (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The content of this study includes a search for Legal aspects of the interdependence between the discretionary power of public administration with principles that are not negated of the interest of judges and legal scholars and that is the principle of proportionality. First, the concept of the discretionary authority of administration is addressed, and then the nature of the principle of proportionality. Thus, it is very necessary to clarify these legal concepts and their developments as a basic criterion for the research itself. Particularly, attention has been given to those concepts in various fields and their connections with each other. On the one hand, the importance of the principle of proportionality with the idea of good governance and the rule of law precedes all the legal principles that the administrative judges apply to the presented facts. And on the other hand, this principle is included in the merits of the precise and deep competence of the administrative judge as it is derived from the principle of appropriateness. Further, the application by the judge inevitably requires more accuracy and deliberation with sufficient awareness of the facts and circumstances of the incident before him. In brief, the principle of proportionality is derived out of the principle of appropriateness. Finally, the legal basis for the association of discretionary power with this principle was addressed, and the correct and realistic opinion in this regard was given careful consideration accordingly.